2015
DOI: 10.1186/s12866-014-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Sm2, a paralog of the Trichoderma cerato-platanin elicitor Sm1, is also highly important for plant protection conferred by the fungal-root interaction of Trichoderma with maize

Abstract: BackgroundThe proteins Sm1 and Sm2 from the biocontrol fungus Trichoderma virens belong to the cerato-platanin protein family. Members of this family are small, secreted proteins that are abundantly produced by filamentous fungi with all types of life-styles. Some species of the fungal genus Trichoderma are considered as biocontrol fungi because they are mycoparasites and are also able to directly interact with plants, thereby stimulating plant defense responses. It was previously shown that the cerato-platani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Indeed, a number of CPs from different filamentous fungi, e.g. SM1, SM2 and Epl1 from the biocontrol agents T. virens and T. atroviride 37404547 as well as BcSpl1 from B. cinerea and a CP from C. platani 2944, were shown to induce both local and systemic disease resistance in host and nonhost plants against different life style pathogens. In the present study, we found that overexpression of MoSM1 in transgenic rice plants confers an improved resistance against two strains representing difference races of M. oryzae and Xoo , as revealed by reduced disease severity and suppressed in planta pathogen growth (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a number of CPs from different filamentous fungi, e.g. SM1, SM2 and Epl1 from the biocontrol agents T. virens and T. atroviride 37404547 as well as BcSpl1 from B. cinerea and a CP from C. platani 2944, were shown to induce both local and systemic disease resistance in host and nonhost plants against different life style pathogens. In the present study, we found that overexpression of MoSM1 in transgenic rice plants confers an improved resistance against two strains representing difference races of M. oryzae and Xoo , as revealed by reduced disease severity and suppressed in planta pathogen growth (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BcSpl1 in Botrytis cinerea and MoMSP1 in Magnaporthe oryzae were found to contribute to the fungal virulence as the knock-out mutants for BcSpl1 or MoMSP1 showed reduced virulence in their host plants303132. Meanwhile, it has also been shown that CPs from both pathogenic and beneficial biocontrol fungi can induce locally and systemically some structural, physiological and molecular defense responses, including initiation of hypersensitive response (HR), accumulation of phenolic compounds and phytoalexins, production of reactive oxygen species (ROS), and upregulation of defense-related genes in host and nonhost plants33343536373839404142434445. SM1 and SM2 from Trichoderma virens , BcSpl1 from B. cinerea , and MoSM1 (also known as MoMSP1) from M. oryzae could induce systemic disease resistance in rice, cotton, maize, tobacco, tomato and Arabidopsis against different pathogens3237384042454647 and the activation of systemic resistance by CP from C. platani and BcSpl1 from B. cinerea was found to be regulated through stomatal perception, overexpression of salicylic acid (SA)- and ethylene-signaling genes and camalexin biosynthesis4446.…”
mentioning
confidence: 99%
“…Despite the fact that CPs are highly represented in fungal genomes, their primary function is not entirely clear, but some species have been demonstrated to be involved as virulence factors or elicitors during plant-pathogenic and symbiotic interactions, respectively. For example, during the mutualistic T. virens-plant interaction, fungal CP elicitors Sm1 (TR_82662, TA_302952, and TV_110852) and Sm2 (TR_123955, TA_88590, and TV_111830) are secreted during the first stages of root sensing and induce systemic disease resistance, conferring resistance to phytopathogens (28,29,1271,1272). In contrast, CP virulence factor BcSpl1 from Botritys cinerea has a phytotoxic function in inducing necrosis on tobacco leaves (1273).…”
Section: Hydrophobins and Cerato-platanin Proteinsmentioning
confidence: 99%
“…27,28 Whether this is solely due to the fact that CPPs such as EPL1 or SM1 effectively signal the presence of a fungus for plants or whether CPPs are directly involved in the physical interaction of fungal hyphae with plant roots remains to be investigated. for epl1 gene knockout strains so far no growth defects or phenotypes related to the formation of hyphae or spores were detected, also not during stress growth conditions such as osmotic stress.…”
Section: Discussionmentioning
confidence: 99%